Cognitive behavioural therapy plus standard care versus standard care for persistent aggressive behaviour or agitation in people with schizophrenia - Ballesteros, Javier; Moreno-Calvete, María Concepción; Santos-Zorrozua, Borja; González-Fraile, Eduardo (Cochrane Database of Systematic Reviews, 2023)
Background: Schizophrenia and other psychoses are thought to be associated with a substantial increase in aggressive behaviour, violence and violent offending. However, acts of aggression or violence committed by people with severe mental illness are rare and circumscribed to a small minority of individuals. We know little about the frequency and variability of violent episodes for people with schizophrenia who present chronic or recurrent aggressive episodes, and of available interventions to reduce such problems. A psychological intervention, cognitive behavioural therapy (CBT), aims to challenge dysfunctional thoughts and has been used since the mid-1970s to improve mental health and emotional disorders. CBT includes different interventional procedures, such as cognitive therapy, elements of behavioural therapy, problem-solving interventions, and coping skills training, among others. Although CBT presents much diversity, interventions are characteristically problem-focused, goal-directed, future-oriented, time-limited (about 12 to 20 sessions over four to six months), and empirically based. CBT has shown clinically beneficial effects in persistent positive and negative symptoms of schizophrenia and its use as an add-on therapy to medication in the treatment of schizophrenia is supported by treatment guidelines. However, several Cochrane Reviews recently concluded that, due to the low quality of evidence available, no firm conclusions can currently be made regarding the effectiveness of adding CBT to standard care for people with schizophrenia, or about CBT compared to other psychosocial treatments for people with schizophrenia. Whereas CBT is not an emergency or crisis intervention that acts immediately on the known or unknown triggers underlying aggressive behaviour, might be a timely treatment used to manage persistent aggression or repeated aggressive episodes in people with schizophrenia. Objectives: To assess the efficacy and safety of cognitive behavioural therapy (CBT) plus standard care versus standard care alone for people with schizophrenia and persistent aggression. Search methods: On 18 January 2023, we searched the Cochrane Schizophrenia Group's Study-Based Register of Trials which is based on CENTRAL, CINAHL, ClinicalTrials.Gov, Embase, ISRCTN, MEDLINE, PsycINFO, PubMed, and WHO ICTRP. We also inspected references of all identified studies for more studies. Selection criteria: All randomised controlled trials comparing CBT plus standard care with standard care alone for people with schizophrenia and persistent aggression. Data collection and analysis: We independently inspected citations, selected studies, extracted data and appraised study quality. For binary outcomes, we calculated risk ratios (RR) and their 95% confidence intervals (CIs). For continuous outcomes we calculated mean differences (MD) and their 95%CIs for outcomes reported with the same measurement scale. Post hoc, for counts over person-time outcomes, we calculated incidence rate ratios (IRRs) and their 95%CIs. If feasible, we combined study outcomes with the random-effects model. We assessed the risk of bias for included studies and created a summary of findings table using the GRADE approach. Main results: We included two studies with 184 participants with psychotic disorder (mainly schizophrenia) and violence. The studies were run in forensic units and prison. Both studies were at high risk of bias on blinding (performance and detection bias). CBT plus standard care as compared with standard care may result in little to no difference in the frequency of physical violence at end of trial (IRR 0.52; 95% CI 0.23 to 1.18) and follow-up (IRR 0.86; 95% CI 0.44 to 1.68). The confidence interval did not exclude the null effect, and the certainty of the evidence is very low due to lack of blinding and to the small sample size. One study reported no deaths in both arms and zero serious and other adverse events. The other study did not report any figure for deaths or adverse events. CBT plus standard care as compared with standard care may result in little to no difference in leaving the study early for any reason (RR 1.04; 95% CI 0.53 to 2.00). Confidence interval did not exclude the null effect and the certainty of the evidence is low due to lack of blinding and the small sample size. Authors' conclusions: Whereas the evidence from only two studies with 184 participants suggests the use of CBT plus standard care may reduce some aggressive behaviours in patients with schizophrenia, the grading of the certainty of the evidence is very low. It implies that there is not yet reliable evidence to guide clinical decisions and therefore more evidence is needed to get a more precise estimate of the effect of the intervention. Currently, we have very little confidence in the effect estimate, and the true effect could be substantially different from its estimate.
Keywords: schizophrenia; cognitive behavioural therapy; persistent aggressive behaviour; Scopus; JCR